2020
DOI: 10.1101/2020.05.27.113977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Discovery of Pseudomonad Genetic Factors Involved in Sensitivity to Tailocins

Abstract: Tailocins are bactericidal protein complexes produced by a wide variety of bacteria to compete against closely related strains. Like tailed bacteriophages, with whom they share an evolutionary and morphological relationship, tailocins bind and kill a narrow spectrum of target cells. Thanks to their high specificity, tailocins have garnered recent attention for their potential as precision antibacterial agents. Nevertheless, the field currently lacks a systematic investigation of genetic determinants of tailoci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Colistin tolerance was associated with increased expression of Pmr proteins that modify LPS to reduce colistin a nity, meaning that only transcriptionally active cells avoid membrane destabilization (27,28,39). Tailocin sensitivity is also linked to the composition of LPS (40), which can vary according to changes in environment and gene expression (41). We recently found that an LPS cluster gene of unknown function affects the frequency of tailocin persisters without impacting tailocin susceptibility or host tness (30).…”
Section: Discussionmentioning
confidence: 99%
“…Colistin tolerance was associated with increased expression of Pmr proteins that modify LPS to reduce colistin a nity, meaning that only transcriptionally active cells avoid membrane destabilization (27,28,39). Tailocin sensitivity is also linked to the composition of LPS (40), which can vary according to changes in environment and gene expression (41). We recently found that an LPS cluster gene of unknown function affects the frequency of tailocin persisters without impacting tailocin susceptibility or host tness (30).…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that LPS is a receptor for some tailocins ( Kutschera et al, 2019a;Kandal et al, 2020), a link between the sensitivity to tailocins and the structural variation in LPS has not been demonstrated until recently. Carim et al (2020) have shown within the genus Pseudomonas that OSA composition and display are the most important contributors to tailocin sensitivity. Our results also indicate a strong but not perfect relationship between tailocin sensitivity and CPA within P. syringae.…”
Section: Discussionmentioning
confidence: 99%
“…Carim et al . (2020) have shown within the genus Pseudomonas that OSA composition and display are the most important contributors to tailocin sensitivity. Our results also indicate a strong but not perfect relationship between tailocin sensitivity and CPA within P. syringae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other antimicrobials, characterization of infectivity and cross-resistance between a panel of phages has been limited to a few model organisms and remained phenomenological until recently(Hudson et al, 1978; Lindberg and Hellerqvist, 1971; Marti et al, 2013; Samuel et al, 1999; Tu et al, 2017; Wright et al, 1980). The advent of genome-wide saturated transposon sequencing (Bohm et al, 2018; Chan and Turner, 2020; Christen et al, 2016; Cowley et al, 2018; Pickard et al, 2013) and the corresponding DNA bar-code based modifications has enabled the high-throughput and low cost genome-scale screening for the genetic determinants of these phenomena(Carim et al, 2020; Mutalik et al, 2019, 2020; Rousset et al, 2018; Wetmore et al, 2015). Since this economically permits the independent screening of many phages against a host library, it is now possible to determine and compare the genes that affect the successful infection of one or more phages.…”
Section: Introductionmentioning
confidence: 99%